6 - Myth and Ceremony: Contested Marketization and Internationalization Regimes in Kenya’s Higher Education - Milton O. Obamba (Journal of Higher Education in Africa, 2009)
The internationalization of higher education, which means integrating an international dimension into the functions and delivery of higher education, is increasingly a matter of immense policy significance for many governments and universities worldwide as higher education becomes a key instrument for international development cooperation and international trade. The past two decades have witnessed tremendous transformations in policy and structure across the sub-Saharan Africa higher education landscape. The defining features of the transformation include: the diversification of sources of funding, privatization and liberalization of the university sector, and severe reductions on government funding of universities across the region. In the Kenyan context, the discourses of global competitiveness, internationalization and pursuit of world-class quality assurance standards have featured prominently in a wide variety of the major recent policy documents. This paper set out to examine the phenomenon of marketization in higher education and explore the complex political economy of educational commodities. It reviews a range of policy discourses and instruments to reconstruct and analyze the growing rhetoric of ‘global’ competitiveness and the phenomenon of internationalization; examining its dynamic and troubled intersections with marketization and expansion within Kenya’s higher education landscape. The paper argues that government policy and university activities strongly emphasize market-oriented logics of expansion and commercialization; but within the context of a highly fragmented and incomplete market landscape. Marketization therefore suitably satisfies the universities’ natural instincts for economic survival at a time of severe financial distress and stiffer competition; while internationalization is utilized as myth and ceremony embellished with policy but not action.